Optimizing the Potential of Wangkelang Village Through Community Participation-Based Mentorship and Socialization - Hendri Hermawan Adinugraha; Mufti Lathif; Masruroh; M. Jauhar Ali; Ayatullah Sadali (PT Pustaka Cendekia Publisher, 2025)
This community service aims to develop the local potential of Wangkelang Village, including the education, economy, and tourism sectors. The village’s potential, which includes natural resources such as Curug Cilawet and the MSME sector, such as local coffee production, has not been optimally utilized due to a lack of community participation, technological literacy, and access to digital marketing. Through the Asset-Based Community Development approach, this program actively involves the community in planning and evaluation. The program includes business management training for MSME players, halal certification and Business Identification Numbers, digital-based tourism development, and educational activities such as early marriage prevention socialization and children’s gross motor training. The results show increased community awareness of the importance of education, product branding, and digitalization. Support from the village government, academics, and local communities is key to the success of this program. Active community participation enables sustainable development of village potential, creating positive impacts through economic improvement, job creation, and strengthening the local identity of Wangkelang Village.